Is hemithyroidectomy a rational management for benign nodular goitre? - (:unkn) unknown (VAN ZUIDEN COMMUNICATIONS, 2015)
Background: The incidence and potential risk factors for the recurrence of benign nodular goitre after unilateral thyroidectomy are not clearly defined. The aim of this study was to assess the rate of progression of nodular goitre in the contralateral thyroid lobe and of hypothyroidism requiring replacement therapy after unilateral thyroid lobectomy for benign nodular goitre. Patients and Methods: Patients who underwent hemithyroidectomy for benign nodular goitre between 2000 and 2009 were included in the study. The primary outcome of this study was the reoperation rate for recurrent goitre, the rate of progression of nodular goitre and the rate of hypothyroidism requiring L-T4 replacement therapy. Clinical factors that have an effect on progression were further analysed. Results: 259 patients were included for study. Progression of the nodular goitre in the remnant lobe was observed in 32% (n = 83) of the patients. However, over time, only 2% of these 83 patients underwent contralateral hemithyroidectomy due to this progression. Fifty-six (22%) patients required L-thyroxin replacement due to persistent hypothyroidism after hemithyroidectomy. The factors shown to affect progression of nodular goitre were advanced age, preoperative hyperthyroidism, preoperative diagnosis of toxic nodular goitre and the presence of surgical indication for a toxic goitre causing hyperthyroidism and a definitive pathological diagnosis of nodular hyperplasia. Conclusion: There was a progression of the nodular goitre in the remnant lobe in about one-third of the patients who underwent hemithyroidectomy. However, only 2% of these patients underwent complementary contralateral hemithyroidectomy due to clinical progression in 31 months of follow-up.
Keywords: Benign nodular goitre; hemithyroidectomy; hypothyroidism; recurrence; MULTINODULAR GOITER; TOTAL THYROIDECTOMY; NONTOXIC GOITER; HYPOTHYROIDISM; RECURRENCE; LOBECTOMY; THERAPY; DISEASE; AREA